Von einen Wand zur Anderen : für Micha Ullman. - Herzogenrath, Wulf; Flügge, Matthias Ochs, Alexander (Nürnberg : Verlag für moderne Kunst, 2009)
Sartorius, Joachim ; Meschede, Friederich ; Grütters, Monika ; Ochs, Alexander ; Flügge, Matthias ; Hoet, Jan ; Schmitz, André ; PietraLöbl, Sr. M. ; Staeck, Klaus ; Hölzl, Daniela ; Lackmann, Thomas ; Joly, Jean-Baptiste ; Newman, Chris ; Hölzl, Cora ; Neubert, Chrishard-Georg ; Stepken, Angelika, Schneegass, Christian ; Rattemeyer, Volker
boek
Keywords: Ullmann, Micha